Collective self-identification of British ICS officers in the interwar period. (Journal of history, 2022)
The article is devoted to the collective self-identification of the officers of the Indian Civil Service, using content analysis and a comparative method. This article aims to reveal the issue of collective self-identification of British ISC officers, their ideology, daily life, and how they saw themselves and others. Under British Rule of India, the role of the connection between the people and the rulers, the symbol of visible power on the ground, was entrusted to the officers of the Indian Civil Service (ICS). Therefore, the article considers the questions of the features of the British character and their sense of self-identification. Moreover, since the officers underwent a serious selection (age limit (from 20 to 24 years old), passing an open exam, two years of training in Britain), only the best of the best could be accepted into the service, which influenced the sense of collective self-identification of officers, their self-awareness elite among elites and their attitude towards the local population. Key words: British Empire, district districts, administration, Indian Civil Service officers, self-identification.